Development of a Series Image-Based Scrapbook Learning Media on the Topic of Various Norms in My Life for Fifth-Grade Elementary School Students - Aprilia Enggar Ratnasari; Fajar Surya Hutama; Nindya Nurdianasari; Ratna Hidayah; Ervan Prasetyo (Universitas Pendidikan Ganesha, 2026)
The limited variation of instructional media in Pancasila Education at the elementary school level has contributed to low learning outcomes and limited student engagement. This study aims to develop and evaluate the validity, practicality, and effectiveness of a series image-based scrapbook learning media. The study employed a Research and Development (R&D) approach using the Borg and Gall development model. The research subjects consisted of students divided into experimental and control groups, supported by a limited-scale trial. Data were collected through observation, interviews, expert validation, tests, questionnaires, and documentation using relevant instruments. Data analysis was conducted through validity assessment, practicality evaluation, and effectiveness testing using comparative analysis. The findings indicate that the developed media demonstrates a high level of validity, is effective in improving learning outcomes, and is practical for use in the learning process. Therefore, the series picture-based scrapbook learning media has implications as an innovative alternative that can be utilized by teachers to create more engaging, contextual, and student-centered learning experiences.